Mrs Craddock - Maugham, W. Somerset (b, 2000)
But, intelligent and sensual, she quickly becomes bored by her oppressively conventional life, and finds her love for her husband slipping away.Originally rejected by publishers, Mrs Craddock was first published only on condition that certain 'shocking' passages were removed
Keywords: Women -- Fiction. -- Social conditions -- England